Pulegone inhibits inflammation via suppression of NLRP3 inflammasome and reducing cytokine production in mice. (4th May 2019) - Yang, Qingxin; Luo, Jie; Lv, Hongjun; Wen, Taoqun; Shi, Boyu; Liu, Xiaobo; Zeng, Nan
Abstract: Context: Pulegone, a key compound in Schizonepeta essential oil, has been identified as an anti-inflammatory. However, its underlying molecular mechanisms on NLR family pyrin domain containing 3 (NLRP3) inflammasome have not been elucidated. Objective: Here, the modulatory effects of pulegone on NLRP3 inflammasome were investigated. Materials and methods: The C57BL/6J mice were randomly divided into five groups: Normal, Lipopolysaccharides (LPS), Dexamethasone (DEX, 5 mg/kg), Pulegone (0.095 and 0.190 g/kg) groups. All mice were challenged by LPS except for the Normal group. Results: A reduced expression of Interleukin-18 (IL-18), Interleukin-1β (IL-1β), Interleukin-5 (IL-5), Tumor necrosis factor-α (TNF-α), Interferon-gamma (IFN-γ), Monocyte chemoattratctant protein-1 (MCP-1), Macrophage inflammatory protein-1β (MIP-1β), Monocyte colony stimulating factor (M-CSF) and Granulocyte-macrophage colony stimulating factor (GM-CSF) in serum were detected in the pulegone groups as compared to the LPS group. In addition, a reduced mRNA and protein expression production of ASC, NLRP3, and Caspase-1 were detected in lungs after pulegone administration. Histological analysis results indicated that the histological changes of lungs caused by LPS were ameliorated by pulegone. Immunohistochemical study showed a decreased positive cell numbers of P2X7R in Pulegone (0.095 and 0.190 g/kg) groups. Conclusion: Pulegone exerts anti-inflammatory effects on LPS-induced sepsis mice via inhibition of the NLRP3 expression.